Influence of Packaging Materials and Storage Conditions on Seed Germination Ability and Biochemical Changes in Some Medicinal Plants of Indian Forests - Tiwari, RajKumar Singh; Chandra, Krishna Kumar; Dubey, Satish; Tripathi, Sachchidanand (Frontiers in Forests and Global Change, 2022)
The forest environment represents a unique ecosystem for medicinal plants and provides congenial growth and development conditions. Over exploitation of these medicinal flora has negatively affected biodiversity in these areas; some of the important plant species are facing local extinction.. Seed is the essential source of regeneration in forests which demands specific growing conditions. Thus, understanding seeds can be linked to conserving forests and their resources. Medicinal plants seeds degrade fast and lose their viability after a few months of harvests and storage. In protecting the genetic integrity of stored samples, seed viability must be retained for prolonged periods. The study deals with the influence of different seed packaging/storage materials (polythene bags, Jute bags, cloth bags, aluminum foil, unburned earthen-pot, burned earthen-pots), storage duration (one, six, twelve months), and temperature (room, 4°C temperature) on seed germination and biochemical activities of seven medicinal plant species viz. A. moschatus, A. paniculata, B. Orellana, O. basilicum, P. zeylanica, P. Corylifolia, and W. somnifera. The germination ability of A. moschatus was maximum when stored in polythene bags, while unburned earthen pots favored the germination of W. somnifera. Out of seven species studied, seeds of four species showed maximum germination ability when stored at room temperature while a low-temperature environment was beneficial for another 3-species studied. The mean difference in total phenolic and flavonoid content was 4.69% and 8.38% higher, respectively, in low temperature than room temperature conditions. The study concluded that species-specific requirement of storage materials with adjustment of storage duration and temperature for higher germination and longer seed viability in medicinal plant species. Experiments using more medicinal plant species would be essential to test such potential effects of storage material, storage duration, temperature, and via changes in seed germination and biochemical activities; our findings provide important insights that can help to guide management plans that aim to preserve seeds of important medicinal plant species for a longer period. Keywords: Biochemical Medicinal plants, Mycoflora, Seed, Storage, Temperature.